Polydopamine-Mediated Protein Adsorption Alters the Epigenetic Status and Differentiation of Primary Human Adipose-Derived Stem Cells (hASCs) - Harati, Javad; Tao, Xuelian; Shahsavarani, Hosein; Du, Ping; Galluzzi, Massimiliano; Liu, Kun; Zhang, Zhen; Shaw, Peter; Shokrgozar, Mohammad Ali; Pan, Haobo; Wang, Peng-Yuan (Frontiers in Bioengineering and Biotechnology, 2022)
Polydopamine (PDA) is a biocompatible cell-adhesive polymer with versatile applications in biomedical devices. Previous studies have shown that PDA coating could improve cell adhesion and differentiation of human mesenchymal stem cells (hMSCs). However, there is still a knowledge gap in the effect of PDA-mediated protein adsorption on the epigenetic status of the MSCs. This work used gelatin-coated cell culture surfaces with and without PDA underlayer (Gel and PDA-Gel) to culture and differentiate primary human adipose-derived stem cells (hASCs). The properties of these two substrates were significantly different, which, in combination with a variation in extracellular matrix (ECM) protein bioactivity, regulated cell adhesion and migration. hASCs reduced focal adhesions by downregulating the expression of integrins such as αV, α1, α2, and β1 on the PDA-Gel compared to the Gel substrate. Interestingly, the ratio of H3K27me3 to H3K27me3+H3K4me3 was decreased, but this only occurred for upregulation of AGG and BMP4 genes during chondrogenic differentiation. This result implies that the PDA-Gel surface positively affects the chondrogenic, but not adipogenic and osteogenic, differentiation. In conclusion, for the first time, this study demonstrates the sequential effects of PDA coating on the biophysical property of adsorbed protein and then focal adhesions and differentiation of hMSCs through epigenetic regulation. This study sheds light on PDA-mediated mechanotransduction.